ANALISIS SELF REGULATED LEARNING DI MASA PANDEMI COVID 19 SISWA KELAS VI SD MUHAMMADIYAH SAMBISARI - Veliya Septa Jayanti; Ummu Nurohmah; Nurohaida Ayu Himawati; Ika Maryani (Universitas Ahmad Dahlan, 2020)
This study aims to determine students' self-regulated learning during the Covid-19 pandemic at SD Muhammadiyah Sambisari. This study used a descriptive quantitative research method. The research subjects were Grade VI students of SD Muhammadiyah Sambisari. The results showed that the self-regulated learning of grade VI Muhammadiyah SD students was in the medium category with a percentage of 13%, high category 40%, and very high category 47%. This shows that self-regulated learning in grade IV at SD Muhammadiyah Sambisari is good, even though the learning has not face-to-face. Good self-regulated learning in a person is also described, as depending on their belief in the ability of themselves to achieve something they want to show.